Risk Governance And Performance: Research On Indonesian And Malaysian Banking - Mouldy Meirene; Etika Karyani (The Indonesian Journal of Accounting Research, 2017)
Abstract: The purpose of this research is to investigate the risk governance associated with bank performance in Indonesia and Malaysia from 2010 to 2014. The risk governance variables used in this study are board size, board meeting, risk committee size, and risk committee meeting. Moreover, the selected sample is using purposive sampling method. Using return on asset (ROA) and Tobin's Q to measure the bank performance, this study proved that risk governance has a positive relationship with return on an asset in Indonesia. These results support the FSB (2013) recommendation on improving the risk governance framework. Special supervision of risk needs to be taken to prevent risks that may occur in the bank's activities. However, this finding also revealed that the more risk committee meetings, the more the value of the company will reduce. The number of risk committee meeting which was held too often on Indonesian banks, actually provide less effective results. Therefore it is lowering the price of bank shares. Meanwhile, the results show the amount of risk in the banking committee meetings in Malaysia have a positive effect on ROA, and the number of risk committees has a positive effect on firm value. Abstrak: Tujuan penelitian ini adalah untuk menyelidiki tata kelola risiko yang terkait dengan kinerja bank di Indonesia dan Malaysia selama periode 2010-2014. Variabel-variabel tata kelola risiko yang digunakan dalam penelitian ini adalah ukuran dewan, rapat dewan, ukuran komite risiko, dan rapat komite risiko. Selain itu, sampel yang dipilih menggunakan metode purposive sampling. Menggunakan laba atas aset (ROA) dan Tobin's Q untuk mengukur kinerja bank , penelitian ini membuktikan bahwa tata kelola risiko memiliki hubungan yang positif dengan return on asset di Indonesia. Hasil ini mendukung rekomendasi FSB (2013) untuk meningkatkan kerangka kerja tata kelola risiko. Pengawasan khusus terhadap risiko harus diambil untuk mencegah risiko yang mungkin terjadi dalam kegiatan bank. Namun, temuan ini juga mengungkapkan bahwa semakin banyak komite risiko semakin banyak nilai perusahaan akan berkurang. Jumlah rapat komite risiko yang terlalu sering diadakan di bank-bank Indonesia, sebenarnya memberikan hasil yang kurang efektif, oleh karena itu menurunkan harga saham bank. Sementara itu, hasil menunjukkan jumlah risiko dalam rapat komite perbankan di Malaysia memiliki efek positif pada ROA dan jumlah komite risiko memiliki efek positif pada nilai perusahaan.